Coupling of CO2 Emissions and Economic Growth Across the U.S. between 2010 and 2015 (London Journal of Research In Science: Natural and Formal, 2025)
To mitigate climate change it will be necessary to reduce greenhouse gas emissions and this transition is likely to involve an impact on economic output. We adopt the U.N. sustainable development indicator 9.4.1, CO2 emissions per unit of value added, to explore the change over time of the value of economic output as CO2 emissions change. CO2/GDP is most often studied at the national level, but data are available for the 2010-2015 time period to estimate CO2 emissions at the county level in the U.S. Available gridded data allow us to calculate emissions by county for 10 economic sectors, and thus to examine the relationship between CO2 emissions in counties and the locations, populations, and economic activity of the counties at very fine geographic scale. We explore the 9.4.1 indicator at both the state and county scales in the U.S for the period 2010 to 2015. These county-level data reveal large heterogeneity with adjacent counties often exhibiting very different trends in CO2/GDP and states also showing diverse patterns of change. Although CO2 emissions were decreasing as GDP increased over this interval in the U.S. as a whole, the same was true in only four-fifths of its states and in only around one-third of its counties. There were many counties in which CO2 increased as GDP declined, or in other combinations of the two variables. Decoupling of CO2 emissions and economic growth was most apparent in counties with a large fraction of their emissions coming from electricity generation while decoupling was less common in counties with large emissions from the industrial sector. Counties from large urban concentrations were more likely to be decoupling of CO2 and GDP. The spatial heterogeneity at the county level suggests the variety and challenges in motivating the decoupling of emissions from economic growth. Understanding the relationship between CO2 and GDP provides insight for future analyses on where to focus efforts to mitigate CO2 emissions and on how to reduce emissions in ways that are sensitive to issues of equity and efficiency.
Keywords: urban flora; urban ecosystem; species occurrence frequency; Shannon index; biodiversity complexity; biodiversity potential.; density; electron; Radius; Electron Neutrino; Proton; Neutron; Up Quark; Down Quark; Table of Nuclear radiuses and densities.; decoupling; CO2/GDP; U.S. county data; SDG indicator 9.4.1